Under pressure: Time management, self-leadership, and the nurse manager - Elizabeth Goldsby; Michael Goldsby; Christopher B. Neck; Christopher P. Neck (Administrative Sciences, 2020)
Decision making by nurses is complicated by the stress, chaos, and challenging demands of the work. One of the major stressors confronting nurses is perceived time pressure. Given the potential negative outcomes on nurses due to perceived time pressures, it seems logical that a nurse manager's ability to lead nurses in moderating this time pressure and in turn to make better decisions could enhance nurse well-being and performance. Paralleling research in the nursing literature suggests that, in order to improve patients' judgement of the care they received, nurse managers should embrace ways to lower nurses' perceived time pressure. In this conceptual paper, we propose a model to help mitigate time pressure on nurse managers and their frontline nurses based on the research regarding time pressure, psychosocial care, time management, and self-leadership. Three metaconjectures and suggested future studies are given for further consideration by organizational and psychological researchers.
Keywords: 350; nurse manager; self-leadership; stress; time pressure